A CRISPR-Cas12a-Assisted Fluorescence Platform for Rapid and Accurate Detection of Nocardia cyriacigeorgica - Liu, Xueping; Qiu, Xiaotong; Xu, Shuai; Che, Yanlin; Han, Lichao; Kang, Yutong; Yue, Yuan; Chen, Shenglin; Li, Fang; Li, Zhenjun (Frontiers in Cellular and Infection Microbiology, 2022)
Nocardia cyriacigeorgica has gradually become a common pathogen in clinical microbial infections. Identification of Nocardia at the species level is essential to assess the susceptibility and pathogenicity of antimicrobials. However, there is no suitable method for rapid and accurate laboratory detection of N. cyriacigeorgica. In this study, we combined PCR amplification with the CRISPR-Cas12a system to establish a novel detection platform, named CRISPR-PCR, and applied it to the detection of N. cyriacigeorgica in clinical samples. The Cas12a protein exhibited collateral cleavage activity following CRISPR RNA binding to specific targets, then indiscriminately cleaved nearby single-stranded DNA, and this was evaluated for diagnostic nucleic acid detection by measuring the fluorescence signal using a fluorescence reader. The assay takes only 2 h, including DNA extraction for 20 min, nucleic acid pre-amplification for 70 min, and fluorescence detection for 20 min. The limit of detection for N. cyriacigeorgica was 10-3 ng and the specificity was 100%. Thus, the N. cyriacigeorgica CRISPR-PCR assay is a rapid and specific method for detecting N. cyriacigeorgica, and the CRISPR-PCR fluorescence detection platform has great potential for detection of other pathogens.